Makna Iṣlāḥ dalam Al-Qur’an: Kajian Semantik Ensiklopedik serta Implikasinya bagi Kehidupan Manusia - Olik Abdul Malik; Solihin; Asep Abdul Muhyi (Al-Bayan: Jurnal Studi Al-Qur'an dan Tafsir, 2026)
Iṣlāḥ is a key Qur'anic concept that signifies comprehensive reform across human life. Its interpretation, however, is often limited to repairing damage or reconciling disputes, leaving its broader semantic relations insufficiently explored. This study examines the meaning of iṣlāḥ and its derivatives in the Qur'an using an Encyclopedic Semantic approach and analyzes their implications for human life. Employing qualitative library research with descriptive-analytical methods, the study traces the diachronic and synchronic development of the concept. The findings reveal that iṣlāḥ and its derivatives occur 180 times in 41 forms across 54 surahs. Its basic meaning refers to improvement, the removal of corruption, and the restoration of proper order as the opposite of fasād. In the pre-Qur'anic period, iṣlāḥ was associated with peace, security, conflict resolution, and social welfare; in the Qur'anic period, it expanded into spiritual, moral, familial, and social dimensions; while in the post-Qur'anic period, it developed toward reform, reconciliation, balance, and the common good. The resulting semantic network positions iṣlāḥ as a comprehensive principle encompassing spiritual transformation, ethical conduct, social harmony, justice, family development, and the protection of vulnerable groups. This study contributes to Qur'anic semantic studies by proposing an encyclopedic framework for understanding iṣlāḥ as a holistic paradigm of reform oriented toward justice, harmony, and the common good.